1993
DOI: 10.1002/hed.2880150212
|View full text |Cite
|
Sign up to set email alerts
|

Surgical strategies for differentiated carcinoma of the thyroid isthmus

Abstract: The postoperative outcome (including clinicopathologic features) in 19 patients with differentiated thyroid cancer of the isthmus was investigated to develop more appropriate surgical strategies for these lesions. The extent of thyroidectomy, including neck dissection, tumor size, nodal involvement, and other clinical features were evaluated. The incidence of intraglandular dissemination was about 16% in all patients. Analysis of regional node metastatic distribution revealed no definite metastatic pattern. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 3 publications
4
31
4
1
Order By: Relevance
“…Between 2006 and 2012, we treated 3557 patients with PTC in our hospital, of whom 73 (2.1%) were histologically diagnosed with solitary PTC limited to the thyroid isthmus, which is similar to previously reported value of 2.5% . Lee et al reported a higher frequency of isthmic PTC (9.2%), but their study included patients with multifocal tumors; the frequency of solitary isthmic PTCs was 4.7% in their study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Between 2006 and 2012, we treated 3557 patients with PTC in our hospital, of whom 73 (2.1%) were histologically diagnosed with solitary PTC limited to the thyroid isthmus, which is similar to previously reported value of 2.5% . Lee et al reported a higher frequency of isthmic PTC (9.2%), but their study included patients with multifocal tumors; the frequency of solitary isthmic PTCs was 4.7% in their study.…”
Section: Discussionsupporting
confidence: 75%
“…Currently, there is no specific guideline for the management of thyroid cancers confined to the isthmus. A few authors have suggested that thyroid isthmusectomy alone or with limited neck dissection (including precricoid and pretracheal lymph node dissection) may be sufficient for the treatment of patients with papillary thyroid carcinoma (PTC) limited to the thyroid isthmus . However, PTC has a propensity for regional lymphatic spread, and most frequently involves the central neck lymph nodes .…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Lim et al reported that patients treated with a total thyroidectomy had an increased RFS when compared to those treated with lobectomy with isthmusectomy (hazard ratio: 0.355; 95% CI: 0.127-0.992). 33 In our study, the 5-and 10-year RFS were very similar to those who had only an isthmusectomy (93.1%), compared to those who had more aggressive thyroid gland surgery (94.6%); DSS were 100.0% in both groups at 10 years. 23 Sugenoya et al's group studied 19 patients with WDTC isthmus malignancies.…”
Section: Discussionsupporting
confidence: 69%
“…PTCs arising in the isthmus are more likely to have multiple foci, capsular invasion, and invasion of adjacent tissues such as the trachea and strap muscles, even with a smaller tumor size, when compared with PTCs located in the lobe 20,21. The multifocality seems to be related to the midline position of the tumors, which easily spread to the bilobes, and more frequent capsular invasion appears to result from tumors growing in the thin thyroid isthmus 9.…”
Section: Discussionmentioning
confidence: 98%